2022
DOI: 10.1097/iae.0000000000003501
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Thickness and Foveal Hypoplasia in Adults Born Preterm With and Without Retinopathy of Prematurity

Abstract: Supplemental Digital Content is Available in the Text.This study investigated the long-term effects of prematurity on macular morphology in adulthood indicating that fetal origins affect foveal shape, resulting in foveal hypoplasia potentially affecting the visual acuity in later life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 31 publications
4
23
0
1
Order By: Relevance
“…From each month from 1969 to 2002, six (3 males and 3 females) randomly selected full‐term subjects with a birth weight between the 10th and 90th percentile were also invited to serve as controls. The study examinations were performed between 2019 and 2021 as reported earlier 27‐35 . The flow chart for eligibility and effective recruitment efficacy proportion is displayed in Figure S1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…From each month from 1969 to 2002, six (3 males and 3 females) randomly selected full‐term subjects with a birth weight between the 10th and 90th percentile were also invited to serve as controls. The study examinations were performed between 2019 and 2021 as reported earlier 27‐35 . The flow chart for eligibility and effective recruitment efficacy proportion is displayed in Figure S1.…”
Section: Methodsmentioning
confidence: 99%
“…The study examinations were performed between 2019 and 2021 as reported earlier. [27][28][29][30][31][32][33][34][35] The flow chart for eligibility and effective recruitment efficacy proportion is displayed in Figure S1. Each recruited participant underwent a detailed ophthalmological examination including Scheimpflug imaging, ocular biometry and a medical history interview.…”
Section: Study Populationmentioning
confidence: 99%
“…Die Proband*innenrekrutierung und der Selektionsalgorithmus sind in Abb. 1S (Zusatzmaterial) sowie an anderer Stelle beschrieben 23 , 24 , 25 , 26 , 27 , 28 , 29 . Alle Teilnehmenden wurden einer detaillierten und umfassenden augenärztlichen Untersuchung unterzogen, einschließlich einer Untersuchung der Refraktionsfehler und einer Befragung zur Krankengeschichte.…”
Section: Patienten/materials Und Methodenunclassified
“…Recruitment of subjects and the selection algorithm are described in Fig. 1S (supplementary material) and at other points 23 , 24 , 25 , 26 , 27 , 28 , 29 . All participants underwent a detailed and comprehensive ophthalmology exam, which included an examination of refractive errors and a medical history survey.…”
Section: Patients/materials and Methodsmentioning
confidence: 99%
“…Following an invitation algorithm, every former preterm newborn with gestational age at birth (GA) ≤ 32 weeks and every second randomly chosen preterm newborn with a GA 33-36 weeks were approached. For each calendar month (from 1969 to 2002), six randomly selected full-term subjects (three males and three females) with a birth weight between the 10th and 90th percentile were invited to serve as controls as reported earlier [31][32][33][34][35][36][37]. The flow chart for eligibility and the effective recruitment efficacy proportion is displayed in Supplementary Fig.…”
Section: Study Populationmentioning
confidence: 99%